Hemodynamic monitoring in pediatric cardiac critical care - Anil Kumar; Reena Khantwal Joshi (Journal of Pediatric Critical Care)
Effective hemodynamic monitoring is essential in the pediatric cardiac intensive care unit for the early detection and management of shock. Clinical evaluation using vital signs, urine output, lactate levels, and base deficit provides initial insight into the balance between oxygen delivery and consumption. Advances in noninvasive techniques, such as enhanced transthoracic echocardiography (incorporating tissue Doppler imaging, three-dimensional imaging, and speckle tracking) and microcirculatory imaging, enable detailed, real-time assessment of cardiac output, preload, and tissue perfusion without the risks associated with invasive catheterization. In cases where noninvasive data are insufficient, invasive methods such as transpulmonary thermodilution and pulse contour analysis (e.g., PiCCO) provide continuous and accurate measurements of cardiac output, global end-diastolic volume, and extravascular lung water. This review addresses current evidence and emerging trends in hemodynamic monitoring, emphasizing the importance of integrating clinical assessments with both noninvasive and invasive modalities to guide targeted interventions and improve outcomes in critically ill children with heart disease.